Fit of anterior restorations made of 3D-printed and milled zirconia: an in-vitro study - Rues, Stefan; Zehender, Nathalie; Zenthöfer, Andreas; Bömicke, Wolfgang; Herpel, Christopher; Ilani, Ali; Erber, Ralf; Roser, Christoph; Lux, Christopher J.; Rammelsberg, Peter; Schwindling, Franz Sebastian (Journal of dentistry, 2023)
Objectives - To evaluate the fit of zirconia veneers made by either 3D printing or milling. - Methods - A typodont maxillary central incisor was prepared for a 0.5-mm-thick veneer and was reproduced 36 times from resin. Restorations were designed with a 20-µm-wide marginal and a 60-µm-wide internal cement gap, and were made from 3D-printed zirconia (LithaCon 3Y 210, Lithoz, n = 24) and milled zirconia (Cercon ht, DentsplySirona, n = 12). For milled zirconia, a drill compensation was needed to give the milling bur access to the intaglio surface. The restorations were cemented, cross-sectioned, and the cement gap size was analyzed by two raters. Inter-rater reliability was studied at 12 3D-printed veneers (intraclass correlation coefficient, ICC, mixed model, absolute agreement). Twelve remaining 3D-printed restorations were compared with 12 milled restorations regarding fit at three locations: marginally, labially, and at the incisal edge (Mann-Whitney U-tests, α<0.05). - Results - Inter-rater reliability was excellent, with an ICC single-measure coefficient of 0.944 (95%-confidence interval: [0.907; 0.966]). Gap sizes (mean ± SD / maximum) were 55 ± 9 / 143 µm at the margins, 68 ± 14 / 130 µm labially, and 78 ± 19 / 176 µm at the incisor edge for 3D-printed veneers. For milled veneers, gap sizes were 44 ± 11 / 141 µm at the margins, 85 ± 19 / 171 µm labially, and 391 ± 26 / 477 µm at the incisor edge. At the margins, the milled veneers outperformed the 3D-printed restorations (p = 0.011). The cement gap at the incisor edge was significantly smaller after 3D printing (p < 0.001). - Conclusions - 3D-printed zirconia restorations showed clinically acceptable mean marginal gaps below 100 µm. Because drill compensation could be omitted with 3D printing, the fit at the sharp incisal edge was significantly tighter than with milling. - Clinical significance - The fit of 3D-printed ceramic anterior restorations meets clinical standards. In addition, 3D printing is associated with a greater geometrical freedom than milling. With regard to fit this feature allows tighter adaptation even after minimally invasive preparation.